Covid-19 and the Call to Sanitize Human Conscience - Prem Xalxo SJ (Warszawskie Studia Teologiczne)
Amidst the unprecedented health crisis, annihilation of economy and social security, and upsurge in the loss of job opportunities caused by Covid-19, the emergence of a dynamic global spirit of collaboration has reinvigorated the human ability to work together to respond collectively to any peril that threatens the integral well-being of the entire humanity. The precautionary measures of washing our hands regularly, sanitizing oneself, using masks and maintaining social distances have rendered new meaning to human relationships. Apart from highlighting danger of dominant technocratic paradigm, the pandemic has also called for the sanitization of our conscience and unmask oneself to let the viruses of egocentric attitude, narcissism, greed, pride and unquenchable thirst for more and better which ultimately leads to the unbridled exploitation of the natural resources. Only a radical change in our life-style, which takes care of the basic needs, hopes, and aspirations of all forms of life, could reinforce and guarantee a better future.